Genotyping of extended-spectrum beta-lactamase-producing Escherichia coli isolated from wastewater of dairy farms in East Java, Indonesia - Fidi Nur Aini Eka Puji Dameanti; Sheila Marty Yanestria; Mustofa Helmi Effendi; Hani Plumeriastuti; Wiwiek Tyasningsih; Emmanuel Nnabuike Ugbo; Rahayu Sutrisno; Muhammad Ali Akramsyah Safri (Veterinary World)
Background and Aim: Extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli in dairy farm wastewater represents a significant threat to environmental and public health due to the dissemination of antibiotic-resistance genes. This study investigates the molecular profiles of ESBL-producing E. coli isolates harboring blaCTX-M, blaTEM, and blaSHV genes from dairy farm wastewater in East Java, Indonesia.